Utility and benefits of sulfonylureas beyond glycemic control - B., Jayakrishnan (International Journal of Advances in Medicine, 2022)
Department of medicine, Educare institute of dental science Malappuram, Kerala and SafeCare clinics, Tirur, Kerala sulfonylureas (SUs) are one of the oldest, time tested and most commonly used oral antidiabetic agent in Type 2 diabetes. Modern SUs like glimepiride and gliclazide XR were preferred over conventional SUs due to its better efficacy and minimal side effects. The use of Modern SUs in the treatment armamentarium of T2DM has evolved, over past few decades. Modern SUs possesses beneficial pancreatic glucose lowering effect and more interestingly extra-pancreatic pleiotropic benefits. This review article discusses on the utility and benefits of SUs beyond glycemic control and explaining on their pleiotropic effects.